The Impact of a Very Short Abstinence Period on Assisted Reproductive Technique Outcomes: A Systematic Review and Meta-Analysis - Federica Barbagallo; Rossella Cannarella; Andrea Crafa; Sandro La Vignera; Rosita A. Condorelli; Claudio Manna; Aldo E. Calogero (MDPI AG, 2023)
Background: Previous studies supported the beneficial effects of a very short abstinence period on sperm quality. This systematic review and meta-analysis aimed to evaluate the effects of a very short abstinence period (within 4 h) on assisted reproductive technique (ART) outcomes. Methods: A literature search was performed using the Pubmed, Scopus, Web of Science, and Cochrane databases. A meta-analysis was performed according to the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) for randomized controlled trials (RCTs). All eligible studies were selected following the PICOS (Population, Intervention, Comparison/Comparator, Outcomes, Study type) model. The following pregnancy outcomes after ART were considered: fertilization rate (FR), implantation rate (IR), clinical pregnancy rate (CPR), live birth rate (LBR), and miscarriage rate (MR). This study was registered on PROSPERO (CRD42023396429). Results: We evaluated 414 records for eligibility, and 7 studies were ultimately included. Our analysis showed that a very short abstinence period significantly increased the IR, CPR, and LBR after ART. No significant differences were found for the FR and MR. Conclusions: A second ejaculation collected very shortly after the first one could represent a simple strategy to improve the results of ART, especially in couples including patients with abnormal sperm parameters.